2013
DOI: 10.4103/2249-4863.123906
|View full text |Cite
|
Sign up to set email alerts
|

A study of prevalence and association of risk factors for diabetic vasculopathy in an urban area of Gujarat

Abstract: Background:Peripheral arterial disease (PAD) is an aftermath of type 2 diabetes posing a significant health problem in developing countries. Its silent progression warrants presymptomatic screening by ankle brachial index (ABI), which cannot be applied to the whole population. We tried to measure the burden of PAD in diabetics of this region correlating various risk factors for it quantitatively and qualitatively.Materials and Methods:From various out-patient departments, 110 known under treatment type 2 diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
2
14
1
Order By: Relevance
“…Earlier study [21] factor for peripheral vasculopathy in this study. Solanki et al [42] has shown significant association between hyperlipidemia with peripheral vasculopathy which is in agreement with our study. ACR (Odd ratio 1.01, 95% CI: 1.00 -1.01, P = 0.004) found to risk factors for peripheral vasculopathy in this study.…”
Section: Risk Factors For Early Neuropathy and Vasculopathysupporting
confidence: 94%
“…Earlier study [21] factor for peripheral vasculopathy in this study. Solanki et al [42] has shown significant association between hyperlipidemia with peripheral vasculopathy which is in agreement with our study. ACR (Odd ratio 1.01, 95% CI: 1.00 -1.01, P = 0.004) found to risk factors for peripheral vasculopathy in this study.…”
Section: Risk Factors For Early Neuropathy and Vasculopathysupporting
confidence: 94%
“… 14 In previous studies, in Type 2 diabetics of our region, we found poor glycemic control and high prevalence of many preventable risk factor. 15 We also found that Type 2 diabetics have more ectopic fat on expense of skeletal muscle that persists even after matching by weight or BMI, both quantitatively and qualitatively. 16 With this propensity, it seems quite worthful to know body composition and body fat, in particular, both quantitatively and qualitatively in not only high-risk obese subjects but also in Type 2 diabetics with respect to current glycemic control.…”
Section: Discussionsupporting
confidence: 57%
“…[2] Our previous studies have documented a high prevalence of macrovascular complication such as vasculopathy and ectopic body fat in type 2 diabetics of our region, who usually had poor disease control and high prevalence of risk factors, many of which were modifiable. [67] We tried to inquest the same with regard to CAN as evaluated by HRV in this study.…”
Section: Discussionmentioning
confidence: 99%